Efectos a la aplicación de tres niveles de fertilización orgánica en la producción de Cilantro (Coriandrum sativum L.) en el cantón Antonio Ante, provincia de Imbabura - Andrade Estévez, Edwin Henry (2012)
The present investigation was carried out in the Neighborhood the Carmelo, land of the Family Dávila Andrade, the same one that is located in Andrade's Parish Marín, canton Antonio Before, County of Imbabura, located to 12 km to the South West of Ibarra. Certified seed of the variety American Long Standing of cilantro of the house Bejo was used that has 98 germination%. The treatments were evaluated, constituted by organic payments, as Bovinaza (10, 15 and 20 Tn/ha), Cuyasa (25, 37.5 and 50 Tn/ha) and worm Humus (25, 37.5 and 50 Tn/ha). The design experimental employee was complete Blocks at random (DBCA), with ten treatments and three repetitions and the variables were subjected to the variancia analysis with the test of Tukey. They were carried out all the necessary agricultural works in the cultivation for their normal development, as; preparation of the floor, siembra, fertilization, watering, control of overgrowths, aporque, control of plagues and illnesses and it harvests. The evaluated data were: plant height to the 15, 30 and 60 days of age of the cultivation, yield and economic analysis.......